The Impact of Workload and Work Environment on Teacher Job Satisfaction in Vocational High Schools: A Case from Pontianak - Tasya (Journal of Business Economics : Needs, Services, and Money, 2025)
This study examines the impact of workload and work environment on teacher job satisfaction at a public vocational high school (SMK) in Pontianak, Indonesia. Job satisfaction is critical as it affects teaching performance and educational outcomes. Using a quantitative approach, data were collected through structured questionnaires from 44 civil servant teachers selected via purposive sampling. The instruments were tested for validity and reliability, and the data were analyzed using multiple linear regression. Results show that both workload (p = 0.002) and work environment (p = 0.047) significantly and negatively influence job satisfaction. The model accounts for 24.4% of the variance in satisfaction (R² = 0.244). Qualitative findings support these results, highlighting issues such as excessive administrative tasks, poor facilities, limited professional growth, and lack of collegial support. These conditions contribute to reduced motivation and morale. The study is limited by its focus on a single school and only two variables, which may limit generalizability. Future research should explore additional factors such as leadership style and compensation across broader samples. Practically, school leaders are encouraged to reduce workload pressure and cultivate a supportive work environment to enhance teacher well-being and job satisfaction